Acceptance of Blended Learning in Executive Education - Silvana Dakduk; Zuleima Santalla-Banderali; David van der Woude (SAGE Open, 2018)
This article evaluates the factors involved in the acceptance of Blended Learning (BL) with executives based on the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model in executive education. The empirical analysis uses data from 307 responses to an online questionnaire by senior and middle-ranking managers. The confirmatory factor analysis and structural equation modeling demonstrated the applicability of the UTAUT2 model in BL in executive education. The results showed that hedonic motivation, performance expectancy, and effort expectancy predict the intention to adopt BL. Results also prove no significant effect on social influence and habits. The relevance of this article is to contribute to the understanding of the factors that influence the intention to adopt BL in a group not typically considered in higher education research.